Investigation of socio-economic factors affecting sustainable rangeland use - Cevher C.; Altunkaynak B.; Köksal Ö; Ataseven Y.; Yavuz G.G.; Gül U.; Ataseven Z.Y. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
This study was carried out in 11 provinces which have more range improvement projects than others in Turkey. The population of this study was the total of the households (producers) in the villages were the study was implemented between 1998-2013. Sampling volume was determined as 719 according to stratified sampling methods, taking into consideration the number of households in the villages. The data obtained were analysed by the methods of Chi-square and Multinomial Logistic Regression and interpretations were made according to the analysis results. It was determined that age and education level of the producers do not have a significant effect on the sustainability of the rangelands. It was found that the effects of the total land (p<0.05) and the aim for ranching on sustainability (p<0.01) were statistically significant. The participation rate in the rangeland improvement works was sufficient (51.5%).In respect to socio-economic factors, it was found that rangeland improvement works were not successful, the sustainability of rangelands could not be continued, rangeland improvement works were not adopted and sustainable rangeland use was not realized by the current rangeland improvement works.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)